2012
DOI: 10.1039/c2sm25859e
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkling and strain localizations in polymer thin films

Abstract: Wrinkles and strain localized features are observed in many natural systems and are useful surface patterns for a wide range of applications, including optical gratings and microfluidic devices. However, the transition from sinusoidal wrinkles to more complex strain localized features, such as delaminations or folds, is not well understood. In this paper, we investigate the onset of wrinkling and strain localizations in a model system of a glassy polymer film attached to a surface of an elastomeric substrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
104
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 24 publications
2
104
2
Order By: Relevance
“…1). Under compression, the film buckles forming a wrinkle pattern that evolves to a complex collection of delamination blisters and wrinkles as compression is increased [21,22]. Upon release of stress, the topography of regions that were highly curved are measured and found to be flat on the order of the surface roughness (∼ 1 nm).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1). Under compression, the film buckles forming a wrinkle pattern that evolves to a complex collection of delamination blisters and wrinkles as compression is increased [21,22]. Upon release of stress, the topography of regions that were highly curved are measured and found to be flat on the order of the surface roughness (∼ 1 nm).…”
mentioning
confidence: 99%
“…shows a single LSCM optical section of a typical sample while under compression (h = 71 nm). The sample shows wrinkles (center), cracks (edge) and delamination (brightest wrinkle peak) as it has been compressed beyond the critical strain for wrinkling, ǫ w , cracking, ǫ c , and delamination, ǫ D [21]. From such an image the wrinkle wavelength can easily be measured, but more importantly, through optical sectioning we also determine the height of each pixel.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Under a biaxial compressive stress, it has been shown that a repetitive wrinkleto-fold transition produces a hierarchical network of folds 11,12 . These patterns are observed in various systems such as glassy polymers 3,13 , polyethylene sheets 2 or foams 14 . Another group of patterns arises in soft layers supported by rigid substrates 1 .…”
Section: Introductionmentioning
confidence: 99%